Impacts on Climate Variations on Environment and Human Health-An Overview (International Journal of Food and Nutritional Sciences, 2022)
Climate change possess major challenges to human society and to Earth systems,ecosystems and thereby affecting human health. Many climate change/variability andextreme weather- associated events, such as sea level rise, hurricanes, and storm surge,as well as other weather extremes, including extreme precipitation and heat waves, havedirect and indirect impacts on Environment and human health. The main view of thisstudy is describing health impacts of the climate change through projected trends inclimate-change-related health. Vulnerability to the risks associated with Climate Changemay exacerbate on going socio-economic challenges